2003
DOI: 10.1051/0004-6361:20030844
|View full text |Cite
|
Sign up to set email alerts
|

Entropy scaling in galaxy clusters: Insights from anXMM-Newtonobservation of the poor cluster A1983

Abstract: Abstract. An XMM-Newton observation of the cool (kT = 2.1 keV) cluster A1983, at z = 0.044, is presented. Gas density and temperature profiles are calculated over the radial range up to 500 h −1 50 kpc, corresponding to ∼0.35 r 200 . The outer regions of the surface brightness profile are well described with a β-model with β = 0.74, but the central regions require the introduction of a second component. The temperature profile is flat at the exterior with a slight dip towards the centre. The total mass profile… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
111
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(135 citation statements)
references
References 68 publications
23
111
1
Order By: Relevance
“…The observed gas profile in the outer regions fits well to a beta-model with a density slope of 3β gas ¼ α gas (where ρ gas ∝ r −α gas ). We use observations that have small uncertainties on the gas-density slope at large radii and that cover our entire cluster mass range (12,(33)(34)(35)(36). 72 M ⊙ ).…”
Section: Observations Analysis and Resultsmentioning
confidence: 99%
“…The observed gas profile in the outer regions fits well to a beta-model with a density slope of 3β gas ¼ α gas (where ρ gas ∝ r −α gas ). We use observations that have small uncertainties on the gas-density slope at large radii and that cover our entire cluster mass range (12,(33)(34)(35)(36). 72 M ⊙ ).…”
Section: Observations Analysis and Resultsmentioning
confidence: 99%
“…However, simulations have shown that the resulting entropy profiles of the simulated groups are much too flat compared to observations (Borgani et al 2005;Younger & Bryan 2007). Therefore the observed lack of iso-entropic core entropy profiles in groups and poor clusters has shown that simple preheating is unlikely to be the sole explanation of the observations (Ponman et al 2003;Pratt & Arnaud 2003). Ettori et al (2004b) using a simulation that included radiative cooling, star formation and supernova feedback, found a significant negative evolution in the normalization of the L X − T and S − T relations in objects selected in the range 0.5 < z < 1.…”
Section: Interpretation Of Scaling Relations With Simulationsmentioning
confidence: 90%
“…The corresponding uncertainties were given by differentiation of the regularised density profile at each point corresponding to the effective radius of the deconvolved temperature profile. Uncertainties on each X-ray mass point were calculated using a Monte Carlo approach based on that of Pratt & Arnaud (2003), where a random temperature was generated at each radius at which the temperature profile is measured, and a cubic spline used to compute the derivative. We only kept random profiles that were physical, meaning that the mass profile must increase monotonically with radius and the randomised temperature profiles must be convectively stable, assuming the standard Schwarzschild criterion in the abscence of strong heat conductivity, i.e., dln T/dln n e < 2/3.…”
Section: X-ray Mass Profilementioning
confidence: 99%